I Certamen Crono-Teatro (2013). Modalidad de andén 1. Días Cruzados - Pygmalión (Pygmalion. Revista de teatro general y comparado, 2025)
I Certamen Crono-Teatro (2013). Modalidad de andén 1. Días Cruzados